(untitled) (Global Journal of Management and Business Research, 2020)
Balance of trade is a key indicator of the health of any open economy. Therefore, every developing economy strives to achieve this. Currency devaluation (depreciation) is seen as an opportunity for the achievement of trade surplus. This paper aims to examine the impact of depreciation and devaluation on trade balance in Algeria, Tunisia, Gabon, South Africa, Zambia, Nigeria, Morocco, Ghana, Malawi, and Burundi. Dynamic Panel Ordinary Least square (DOLS) method and Toda-Yamamoto for impulse response analysis are employed to predict the effect of depreciation on trade balances as well as the response of trade balances to shocks from depreciation. The results show that depreciation negatively affects the trade balance in the long run and shows that there is no evidence of the J-curve in the selected countries. Moreover, the result for the impulse response function shows that trade balances respond negatively to shocks in exchange rate.